2014
DOI: 10.1371/journal.pone.0112201
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Is Not Associated with Improved Progression Free Survival in Cetuximab Treated KRAS Mutant Metastatic Colorectal Cancer Patients: Results from the CAIRO2 Study

Abstract: Statins may inhibit the expression of the mutant KRAS phenotype by preventing the prenylation and thus the activation of the KRAS protein. This study was aimed at retrospectively evaluating the effect of statin use on outcome in KRAS mutant metastatic colorectal cancer patients (mCRC) treated with cetuximab. Treatment data were obtained from patients who were treated with capecitabine, oxaliplatin bevacizumab ± cetuximab in the phase III CAIRO2 study. A total of 529 patients were included in this study, of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 22 publications
1
40
1
Order By: Relevance
“…After exclusion of unrelated articles, 47 full‐text articles were further reviewed according to preset inclusion and exclusion criteria. Finally, 14 studies involving 130 994 patients met our criteria and were included in this meta‐analysis . Detailed characteristics of the included studies were summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After exclusion of unrelated articles, 47 full‐text articles were further reviewed according to preset inclusion and exclusion criteria. Finally, 14 studies involving 130 994 patients met our criteria and were included in this meta‐analysis . Detailed characteristics of the included studies were summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of the included studies were summarized in Table . Generally, six studies involving 86 622 patients reported survival outcomes for patients of pre‐diagnostic statin uses, while 11 studies involving 44 322 patients investigated survival outcomes related to post‐diagnostic statin uses . Eight studies were conducted in Europe (United Kingdom, Denmark, Netherland, Germany), four in North America, and two in Asia (China, Korea) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations